Students’ Perspectives of YouTube as a Learning Media in Indonesian Language Course - Lely Dian Utami; Enik Rukiati (P3M Politeknik Negeri Jember, 2022)
COVID-19 pandemic has caused a lot of changes in all fields, including the field of education. Online learning has been implemented as a way to conduct teaching and learning process remotely. Therefore, the learning methods and media that teachers use have to be adapted to online learning. YouTube is one of media that teachers can use in online learning. The purpose of this study is to determine the response of English students at State Polytechnic of Jember to the use of instructional media via YouTube as a learning resource for Indonesian language course. This research used quantitative research methods. The results of the questionnaire distributed online to students via Google Form will then be analyzed quantitatively descriptively. The results of the study show that the students can learn information easily in a coherent manner from YouTube. Also, they are more motivated and interested in learning. More importantly, they have an interesting learning experience. In conclusion, they students gave good responses to the use of YouTube as a learning resource.